1993
DOI: 10.1002/bjs.1800800829
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of systematic lymph node dissection in gastric carcinoma

Abstract: In a prospective multicentre study of 2394 patients with gastric carcinoma the prognostic relevance of systematic lymph node dissection was evaluated. Of 1654 patients undergoing resection, 558 had a standard lymph node dissection, defined as fewer than 26 nodes in the specimen, and 1096 underwent radical lymphadenectomy, i.e. 26 or more nodes in the specimen. Radical dissection significantly improved the survival rate in patients with Union Internacional Contra la Cancrum (UICC) stages II and IIIA tumours. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
214
2
24

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(261 citation statements)
references
References 14 publications
21
214
2
24
Order By: Relevance
“…Our results are similar to those previously reported by Pacelli et al (1993) in their retrospective trial and by Siewert et al (1993) in their prospective nonrandomised trial.…”
Section: Survival Of Igcsg D2 Gastrectomy Phase II Study M Degiuli Et Alsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are similar to those previously reported by Pacelli et al (1993) in their retrospective trial and by Siewert et al (1993) in their prospective nonrandomised trial.…”
Section: Survival Of Igcsg D2 Gastrectomy Phase II Study M Degiuli Et Alsupporting
confidence: 93%
“…Favourable patient survival after D2 gastrectomy has also been reported by some other non-Japanese retrospective nonrandomised trials (Pacelli et al, 1993;Siewert et al, 1993).…”
supporting
confidence: 67%
“…These findings were confirmed by another German study (Siewert et al, 1993). They prospectively registered and analysed gastrectomies with extended lymphadenectomies in 19 hospitals, of which 16 were university hospitals and concluded that radical lymphadenectomy (> 26 nodes) improved survival rate compared to < 26 nodes.…”
Section: Discussionmentioning
confidence: 67%
“…In the West, the higher prevalence of proximal gastric cancers, and patient factors such as older age, higher body mass index and higher incidence of comorbidities make the surgical management more challenging,15, 16, 17 has perhaps resulted in the tradition of carrying out a more limited lymph node dissection. Despite this, there is now a wider uptake of extended lymphadenectomy in countries other than Japan, and this is thought to be behind the significant improvement in long‐term survival 18, 19, 20, 21, 22…”
Section: Gastric Surgerymentioning
confidence: 99%